2009
DOI: 10.1007/s10549-008-0292-y
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk in relation to the joint effect of BRCA mutations and diet diversity

Abstract: It has been suggested that gene-environment interaction is related to the risk of cancer. To evaluate departure from multiplicative effects between BRCA mutations and diet diversity in breast cancer (BC), a case-only study was carried out in a French-Canadian population including 738 patients with incident primary BC comprising 38 BRCA mutation carriers. Diet diversity was assessed using a validated food frequency questionnaire. Unconditional logistic regression analysis was performed to assess case-only odds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…The risk associated with BRCA mutations is so high that women are now recommended prophylactic total mastectomy, but a century ago the risk in women with the same mutations would have been approximately equivalent to that of women in the general population of North America and Western Europe today. Recent studies of French-Canadian families with inherited BRCA1/2 mutations have examined the aspects of lifestyle associated with breast cancer risk and found that total energy intake and weight gain since the age of 18 were positively associated with risk [159] and dietary vegetable and fruit diversity were negatively associated [160]. These studies indicate that exposures that determine progression to clinical disease can have a large effect and operate independently of the initiating factors.…”
Section: Environmental Exposuresmentioning
confidence: 99%
“…The risk associated with BRCA mutations is so high that women are now recommended prophylactic total mastectomy, but a century ago the risk in women with the same mutations would have been approximately equivalent to that of women in the general population of North America and Western Europe today. Recent studies of French-Canadian families with inherited BRCA1/2 mutations have examined the aspects of lifestyle associated with breast cancer risk and found that total energy intake and weight gain since the age of 18 were positively associated with risk [159] and dietary vegetable and fruit diversity were negatively associated [160]. These studies indicate that exposures that determine progression to clinical disease can have a large effect and operate independently of the initiating factors.…”
Section: Environmental Exposuresmentioning
confidence: 99%
“…The research revealed a strong and significant interaction between BRCA mutations and diversity of vegetable and fruit intake (COR=0.27; 95 % CI=0.10-0.80; P=0.03) when the upper quartiles were compared to the lower quartiles. The authors concluded that vegetable and fruit diversity may be associated with a significant reduced risk of breast cancer among women with BRCA mutations [63].…”
Section: Nutritionmentioning
confidence: 99%
“…Specifically, BMI was associated with BRCA-related breast cancer risk, and high diet quality was associated with a low risk of BRCA-related breast cancer (7)(8)(9). In addition, some studies reported that vegetable and fruit intakes were modifiers in developing breast cancer in BRCA mutation carriers (10). However, these findings are limited to Western populations.…”
Section: Introductionmentioning
confidence: 99%